2015
DOI: 10.18632/oncotarget.5310
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of IKKβ expression in glioma-infiltrating microglia/macrophages is associated with defective inflammatory/immune gene responses in glioblastoma

Abstract: Glioblastoma (GBM) is an aggressive malignancy associated with profound host immunosuppression. Microglia and macrophages infiltrating GBM acquire the pro-tumorigenic, M2 phenotype and support tumor invasion, proliferation, survival, angiogenesis and block immune responses both locally and systematically. Mechanisms responsible for immunological deficits in GBM patients are poorly understood. We analyzed immune/inflammatory gene expression in five datasets of low and high grade gliomas, and performed Gene Onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 54 publications
(75 reference statements)
3
55
0
Order By: Relevance
“…Microglia and macrophages that accumulate in glioblastomas express MHC II as demonstrated previously (10, 41, 42). Moreover, we demonstrated that tumor-associated MDSCs exhibited higher expression of MHC II than did microglia and macrophages, confirming the recently described characteristics of MDSCs in a large cohort of glioblastoma patients (43).…”
Section: Discussionsupporting
confidence: 78%
“…Microglia and macrophages that accumulate in glioblastomas express MHC II as demonstrated previously (10, 41, 42). Moreover, we demonstrated that tumor-associated MDSCs exhibited higher expression of MHC II than did microglia and macrophages, confirming the recently described characteristics of MDSCs in a large cohort of glioblastoma patients (43).…”
Section: Discussionsupporting
confidence: 78%
“…The lack of genes related to "immune response/activation" in whole tumor tissues of high grade versus low grade glioma has previously been reported (Mieczkowski et al, 2015). This overlap includes genes related to "extracellular matrix organization" and "cell adhesion", but was primarily restricted to genes related to "mitotic cell cycle regulation".…”
Section: Discussionmentioning
confidence: 85%
“…NF-kB signaling in immune cells is likely necessary for maintaining anti-tumor immunity. In one example, decreased levels of IKKβ in glioma-associated microglia/macrophages (GAMs) from glioblastoma multiforme correlated with impaired NF-κB dependent immune and inflammatory response (85). The dichotomy between promoting anti-cancer immunity and blocking tumor cell specific NF-kB signaling presents a conundrum for therapeutic targeting of this pathway, and further emphasizes the need to identify tumor-specific drivers to target.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%